Discussions on sensitive issues - Sutterby, John A., 1966- (Advances in early education and day care ;, 2015)
It is important that early educators view sensitive topics not as problems, but as subjects that are part of our global society. Early educators need to engage children in conversations in which to consider and share diverse perspectives. Early educators also should examine their own experiences when addressing these serious issues. This volume contains chapters that invite conversations about sensitive issues to help educators, children and families use real-life experiences to construct knowledge about their world and other people.